(3GdfgGjI aj bQGAI GdCFeI GdKdGK GdRGFOI Ydi GdYTQI GdbQGAGJ GdTGPIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g` s
(3ChdgG (B:s
(3HOCJ HMeO Gddg fXej GhdG hCgOj UdhGJj ddfHj ef JdG (B- (3hHYO aNP fXej MQha KdGKI Ydi GdYTQ bO RGOJ hcf eJCedGs
(3BNQgG (B:s
(3haj QeVGf GdNjQ Pj GdLhO hGdYdG HCbUi LQGO GdQhe ef CQV HQhSI (B- (3HefRd MGL eDef (B( ) (3dG hHYO UdhGJ hGdSdGe Ydi GdfHj hGdBd (B- (3hCUMGH GdcQGe hef JdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 687s
(3cTa GdXfhf (B2/ 1323s
(3TPQGJ GdPgH (B7 / 204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs